Registration of 'CA 4014' and 'CA 4015' cotton cultivars. Issue 2 (12th April 2022) - Maeda, Andrea B.; Kelly, Carol; Wyatt, Zane Cole; Hague, Steve; Morgan, Valerie; Dever, Jane
Abstract: Organic cotton ( Gossypium hirsutum L.) production in the United States is steadily growing because of increased consumer demand, market premium prices, and regulatory shifts. As organic production expands in the United States, adventitious presence of genetically engineered (GE) traits caused by either pollen‐ or seed‐mediated gene flow from nonorganically grown sources of cotton raises concerns about maintenance of purity requirements, either when marketing cotton or producing planting seed. Adapted cultivars with simply inherited, codominant leaf shape (okra‐leaf) distinct from commercial GE cotton cultivars represent an alternative strategy for maintaining purity through visual roguing, instead of expensive molecular testing. The Texas A&M AgriLife Research cotton breeding program in Lubbock, TX, developed two okra‐leaf cultivars adapted to organic production in the Texas High Plains. Cotton accession (CA) is the designation used for material developed in the Lubbock program. Cultivars 'CA 4014' (Reg. no. CV‐147, PI 699625) and 'CA 4015' (Reg. no. CV‐146, PI 699626) derived from 2014 crosses, individual plant selection followed by modified bulk selection, and 3 yr of replicated performance testing. CA 4014 and CA 4015 have similar yield and fiber quality to the cultivars currently used in Texas organic cotton production, with the advantage of a distinct and uniform morphological marker (okra‐leaf) that enables the identification and elimination, in the field, of off‐types. Core Ideas: Demand for organic cotton is increasing, and U.S. production is concentrated in the Texas High Plains. Maintaining purity expectations from genetically engineered traits in a concentrated cotton production region is difficult. Cultivars suited for organic production with a distinct visual morphological marker aid organic seed production.